Measuring bilateral spillover and testing contagion on sovereign bond markets in Europe - Peter Claeys; Bořek Vašíček (European Central Bank (ECB), 2014)
The global financial crisis rapidly spread across borders and financial markets, and also distressed EU bond markets. The crisis did not hit all markets in the same way. We measure the strength and direction of linkages between 16 EU sovereign bond markets using a factor-augmented version of the VAR model in Diebold and Yilmaz (2009). We then provide a novel test for contagion by applying the multivariate structural break test of Qu and Perron (2007) on this FAVAR detecting significant sudden changes in shock transmission. Results indicate substantial spillover, especially between EMU countries. Differences in bilateral linkages are due to a combination of fiscal trouble and a large banking sector, as Belgium, Italy and Spain are central to shock transmission during the financial crisis. Contagion has been a rather rare phenomenon limited to a few well defined moments of uncertainty on financial assistance packages for Greece, Ireland and Portugal. Most of the frequent surges in market co-movement are driven by larger shocks rather than by contagion.
Keywords: G12; C14; E43; E62; H62; H63; 330; Contagion; eurozone; FAVAR; financial crisis; fiscal policy; spillover